Perubahan metabolisme dan peran radikal bebas pada iskemia miokard - Dyana Sarvasti (Jurnal Kardiologi Indonesia, 2015)
Myocardial ischemic results from severe impairment of coronary blood supply and produces a spectrum of clinical syndromes. It results in a characteristic pattern of metabolic and structural changes that leads to extremely complex situations, which have been extensively studied in recent years. A detailed understanding is now available of the complexity of the response of the myocardium to an ischemic insult. Reperfusion is the most effective way to treat the ischaemic myocardial. But, restoration of flow, however, might result in numerous other negative consequences, thus directly influencing the degree of recovery. Much evidence shows that during the period of myocardial ischemia and reperfusion can occur various changes both in terms of metabolic, electrical, histology, structural, and physiological. Pathological changes in the form of metabolic changes and the role of free radicals on the condition of ischemia and reperfusion injury will be discussed. There are several potential manifestations and outcomes associated with myocardial ischemia and reperfusion.